Exploring the dimensionality of the CLASS Pre-K in Latine preschool classrooms: further support for a bifactor model - Kim, Hanjoe; Gonzalez, Jorge E. (Frontiers in Education, 2025)
IntroductionThe Classroom Assessment Scoring System (CLASS) is a classroom observational tool commonly used to evaluate both structural and process elements of a classroom. Despite its widespread use, over the last decade, debates about its factor structure across various cultural contexts or settings have arisen. In this study, we asked the question, does the CLASS Pre-K retain its established three-domain structure when applied to classrooms with both Latine teachers and preschool children as compared to its original validation in broader U.S. populations? Six alternative models that were suggested by literature were explored.MethodsUsing a series of confirmatory factor analyses, we found that a best fitting bifactor model with one generic factor (Responsive Teaching) and three correlating specific factors (Emotional Support, Classroom Organization, Instructional Support) aligned with the developer’s theorizing was a good fit for the data.ResultsThe generic factor represents a common dyadic systems-level property across all CLASS Pre-K dimensions, which can be characterized by the construct of responsivity.DiscussionFurthermore, Latine cultural values such as bien educado and educación are illustrated as a plausible explanation of the factor structure found in this study. Caution should be exercised in using the CLASS Pre-K in classrooms with cultural backgrounds that differ from the original norming sample, as its domains may not fully capture or accurately reflect culturally specific teacher-child interactions.